2005
DOI: 10.1039/b504479k
|View full text |Cite
|
Sign up to set email alerts
|

Photo-switched wettability on an electrostatic self-assembly azobenzene monolayer

Abstract: A simple electrostatic self-assembly technique was used to fabricate a photo-switched azobenzene monolayer, on which superhydrophobicity and a large reversible CA change could be realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(119 citation statements)
references
References 27 publications
4
115
0
Order By: Relevance
“…This results in the surface roughening shown and the microstructure responsible for the changing of the substrate to a hydrophilic condition. It has been shown that the surface roughness can be an effective tool for changing the contact angle [14]. A similar structure here is believed to be created, and that this causes the change to hydrophilicity as it is supported by figure 3 (a) and (b).…”
Section: Discussionsupporting
confidence: 62%
“…This results in the surface roughening shown and the microstructure responsible for the changing of the substrate to a hydrophilic condition. It has been shown that the surface roughness can be an effective tool for changing the contact angle [14]. A similar structure here is believed to be created, and that this causes the change to hydrophilicity as it is supported by figure 3 (a) and (b).…”
Section: Discussionsupporting
confidence: 62%
“…48,49 After activation of a patterned silicon wafer, azobenzene-containing polymers can be spin or dip coated onto the surface. Isomerisation of trans-azobenzene into the cis-isomer leads to large changes in wettability, depending on the spacing of the pillars.…”
Section: Photoresponsive Wettabilitymentioning
confidence: 99%
“…Recently an azobenzene copolymer assembled into polyelectrolyte multilayer showed a modest 21 change in contact angle with UV light irradiation. However, when the same copolymer was assembled onto a patterned substrate, the change in contact angle upon irradiation was enhanced to 701 (Jiang et al, 2005). It is well established that surface roughness plays a role in contact angle and many systems can be optimized to give rise to a large change in surface properties.…”
Section: Macroscopic Motionmentioning
confidence: 99%